2006
DOI: 10.1021/cm061020o
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Kinetic Studies on Hexagonal Tungstates

Abstract: Formation of nanostructured hexagonal alkali tungstates (HTBs) from ammonium metatungstate (AMT) and alkali chlorides has been investigated by a combined strategy encompassing in situ spectroscopic techniques and hydrothermal synthetic studies. They demonstrate how the morphology of the HTBs can be tuned by the straightforward hydrothermal reaction of ammonium metatungstate with the choice of appropriate alkali chlorides. The resulting particle shapes vary from highly anisotropic fibers to multilevel assemblie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 57 publications
3
46
0
1
Order By: Relevance
“…In addition, it is noted that the dense incubation layer of our films acts as a binder between the nanotree arrays and the substrate, leading to good adhesion to the substrates. Further, the addition of alkali salts in a hydrothermal solution was very important for the formation of nanostructure of WO 3 [ 19] They reported that the smaller cations led to fibrous structure with microscale length, while the larger cations yielded stacked nanorods with hierarchical patterns. In addition, Gu et al synthesized WO 3 nanostructure by adding metal salts in a hydrothermal solution, and Rb 2 SO 4 led to nanorod and nanoplate structures, whereas K 2 SO 4 led to ribbonlike structures.…”
mentioning
confidence: 99%
“…In addition, it is noted that the dense incubation layer of our films acts as a binder between the nanotree arrays and the substrate, leading to good adhesion to the substrates. Further, the addition of alkali salts in a hydrothermal solution was very important for the formation of nanostructure of WO 3 [ 19] They reported that the smaller cations led to fibrous structure with microscale length, while the larger cations yielded stacked nanorods with hierarchical patterns. In addition, Gu et al synthesized WO 3 nanostructure by adding metal salts in a hydrothermal solution, and Rb 2 SO 4 led to nanorod and nanoplate structures, whereas K 2 SO 4 led to ribbonlike structures.…”
mentioning
confidence: 99%
“…[26] We have applied this strategy on the alkali chloride-assisted growth of hexagonal tungsten oxides. [16] Here, the particle morphology and degree of organization of the obtained alkali tungstate nanorods varies with the alkali cationalbeit not as pronounced as in the case of the mixed hexagonal W/Mo-oxides, e.g. their tungsten-based analogues do not display the organization into hierarchical spheres.…”
Section: Understanding Materials: In Situ Investigation Of Oxide Nanomentioning
confidence: 75%
“…[15] Moreover, they can also exert a stabilizing effect via the incorporation into an otherwise unaltered open structural motif. [16] Oxides with such versatile structures are, for example, found among the W-, Mo-and V-containing transition metal oxides that also excel through their high application potential, e.g. in catalysis, sensor and battery technology.…”
Section: Materials Synthesis: Hydrothermal Tuning Of Oxide Nanomaterimentioning
confidence: 99%
See 2 more Smart Citations